Forensic laboratory management applying business principles - Dale, Mark; Becker, Wendy S. (CRC Press/Taylor & Francis, 2015)
The authors present a performance model with seven recommendations to implement, illustrating how forensic managers can serve as leaders and strategically improve the operation and management in scientific laboratories.